(untitled) (Práxis Educativa, 2017)
Understanding the conditions that can promote professional teacher development is extremely relevant, especially in the perspective of providing subsidies for the planning of contexts for this purpose. In this work, we had the objective of investigating the trajectory of two Physics teachers when interacting with two formative contexts (Professional Master’s and Teaching Initiation Scholarship Institutional Program - PIBID) differentiated in terms of requirements and possibilities of professional teacher development. Through semi-structured interviews, we obtained the necessary elements to reconstruct the trajectory of these teachers during their participation in those contexts based on Narrative Analysis associated with another procedure coming from Sociology, which is the Sociological Portrait. To reconstruct the history of these teachers we took into account the concept of individual heritage of dispositions addressed by Bernard Lahire (2005), as well as the dimensions of professional development proposed by Barolli et al. (2017). Our results indicate that it is not enough to propose a context that follows the guidelines of the literature in the sense of not being guided, for example, only in the guidelines of a technical rationality, so that the subject develops professionally. Deep changes seem to require conditions that have been closely linked to the particularities of subjects and contexts. Keywords: Teacher professional development. Dispositions. Formative contexts.